Reconciliation and Relational Continuity: Social Stabilization as a Conceptual Lens on Jingitiu Communal Practices in Sabu Raijua - Rohi, Chandra Ikatyas Widiastuti; Lattu, Izak Yohan Matriks; Setyawan, Yusak Budi (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Formal or symbolic reconciliation does not necessarily ensure the continuity of repaired relationships. Existing scholarship addresses forgiveness, intergroup contact, structural constraints, social reintegration, and everyday peace, but the mechanisms through which relational order is maintained remain distributed across these bodies of literature. This article examines how documented Jingitiu communal practices in Sabu Raijua, Indonesia, can inform this problem and develops social stabilization as a provisional analytical category. The study combines qualitative document analysis with an integrative conceptual review. Its documentary corpus comprises scholarship on reconciliation and peacebuilding together with published ethnographic, historical, and community-based documentation concerning Jingitiu belief, ritual practice, customary authority, and communal life. The comparative analysis identifies four documented features potentially relevant to relational continuity: continuing customary authority, repeated communal participation, collective memory, and a shared moral framework. These features do not demonstrate a standardized Jingitiu reconciliation procedure or causal effects on long-term peace. Instead, they provide a context-bound basis for conceptualizing how repaired relationships may be maintained through recurring institutions, practices, and systems of meaning. Social stabilization is therefore proposed as a heuristic lens rather than a confirmed chronological stage or measured outcome of reconciliation. Direct observation of disputes, interviews with the parties involved and Mone Ama members, and longitudinal research are required to examine its empirical operation and its relationship to power, exclusion, and justice.